Edukasi Kesehatan Mata (E-KeMas) pada Komunitas Remaja Putri: Edukasi Kesehatan Mata (E-KeMas) pada Komunitas Remaja Putri - Sari, Fransiska Novita; Novita Sari, Fransiska; Floriana Ping, Maria (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2024)
Personal ownership of gadgets among teenagers can be a risk factor for eye health problems. This condition can cause gadget addictive behavior, especially in young women who live in the same community. One effort to increase knowledge is through health education. This community service activity aims to increase teenagers' knowledge about how to maintain eye health. The activity method consists of pre-test, lecture, discussion and post-test. The knowledge results showed an increase in the pre-test score in the good knowledge category from 35,71% to 73,80% in the post-test. It is hoped that this activity can be a form of education that the community can provide every time they accept new members in an effort to maintain eye health.